High prevalence of bla CTX-M and bla SHV among ESBL producing E. coli isolates from beef cattle in China’s Sichuan-Chongqing Circle - Yu-Long Zhang (Nature Portfolio, 2021)
Abstract Enterobacteria that produce extended-spectrum β-lactamase (ESBL) such as Escherichia coli (E. coli) are common in our environment and known to cause serious health implications in humans and animals. β-lactam antibiotics such as penicillins, cephalosporins and monobactams are the most commonly used anti-bacterials in both humans and animals, however, Gram negative bacteria (such as E. coli) that produces extended-spectrum β-lactamases (ESBLs) have the ability to hydrolyze most β-lactams therefore making them resistant to β-lactam antibiotics. Recent extensive researches on the epidemiology and genetic characteristics of extended-spectrum β-lactamase (ESBL)-producing E. coli reported the existence of ESBL-producing E. coli in humans, companion animals and poultry. Therefore, this experiment was performed to investigate the prevalence and genetic characteristics of β-lactamase producing E. coli isolated from beef cattle farms in the Sichuan-Chongqing circle of China. Phenotypic confirmation of ESBL-producing E. coli was performed using the double disk synergy test. Polymerase Chain Reaction (PCR) was used to detect bla CTX-M, bla SHV and bla TEM gene codes, then after, isolates were divided into different phylogenetic groups and multi-locus sequence typing (MLST). The results showed that out of the 222 E. coli strains isolated from the beef cattle, 102 strains showed ESBL phenotypes. The PCR results showed that bla CTX-M was the predominant ESBL gene identified among the E. coli strains with 21 (9.5%) isolates having this gene, followed by bla SHV which was found in 18 (8.1%) isolates. The majority of these ESBL positive isolates were assigned to phylogroup A (19.8%) followed by phylogroup B1 (13.5%). In addition, from the MLST results on ESBL positive isolates (n = 30) we identified 19 STs, ST398 (ST398cplx) and ST7130 which were the prevalent population (20%). In conclusion, the high prevalence of CTX-M, and SHV in the study confirmed its association with E. coli infection; therefore, this calls for health concerns on ESBL-producing E. coli. As far as we know, this is the first comprehensive research report relating to ESBL-producing E. coli incidence in Chinese beef cattle.